Smart Contracts and Related Collection Terms - Al-Omari, Sumaia Ali Mohammad (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: The research aims to highlight the most important “financial receipts” provisions in smart contracts through block chain technology. To that end, the study investigated this topic through three claims: first; smart contracts, second; the relationship between smart contracts and block chain, and the third is the provisions of financial receipt within smart contracts. Methods: the Research adopted the descriptive approach through describing smart contracts in terms of their nature and relation to block chain technology, and the inductive approach by tracing this technology from the specialized research, the analytical approach has also been used to analyze the contractual processes in which they take place and the way they are received to reach appropriate legal provisions Results: The study found that any financial receipt made in smart contracts is a bylaw receipt that takes the provision of a bank entry, and that the price of a valuator's financial receipt through digital signatures adopted by the WTO World Trade Organization as a means of recording property. The study also found that, unlike contracts conducted through public networks, smart contracts conducted through private networks were those that met legitimate conditions. Conclusions: The study recommends benefiting from experiences of countries that have adopted these contracts in their modern system, thus helping to avoid many of the problems they face.